Towards Comprehensive Tsunami Mitigation Study: a Case of Legundi Island - Elsa Rizkiya Kencana; Mustarakh Gelfi; Hendra Achiari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Sunda Strait Tsunami happened in December 2018 due to a flank collapsed of Mount of Anak Krakatoa. Lampung Province was affected by Sunda Strait Tsunami at various locations that close to Mount of Anak Krakatoa. The research is conducted to modelling the tsunami wave that happened at Legundi Island in 1D model using SwanOne software. The methodology of the research is using data input from bathymetric survey and apply the wave transformation equations in the nearshore using SwanOne software to do the 1D model. There are four scenarios to do the wave modelling. All scenarios consider from former study about Sunda Strait Tsunami 2018. The results from all scenarios are verified by prior research from Takabatake (2019) of inundation height in Legundi Island, it is 3,34 m. The result shows the inundation height from wave modelling is a combination of wave height (1,533 m), water depth (1,658 m) and wave setup (0,215 m), and the outcome is 3,406 m. The model shows a fine result because the percentage error of the model is only 0,769%, which is below 5%. This research can be a good approach for another wave modelling in other locations and also to do further research to wave modelling in 2D model.